Peran Bidan Dalam Memberdayakan Nenek Sebagai Caregiver Cucu Melalui Edukasi Gizi Dan Kesehatan Anak - Yarnita Yarnita; Andi Nursiah; Endang Ernandini; Kasmiati Kasmiati (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The modern family structure has shifted, leading many children to be cared for by their grandmothers due to parental work demands. This situation requires grandmothers to have sufficient understanding of child nutrition and health care. This community service program aimed to empower grandmothers as caregivers through education on balanced nutrition and early childhood health. The methods included interactive lectures, group discussions, menu-planning demonstrations, and leaflet distribution. The program took place in Village X, under the supervision of Community Health Center Y, involving 35 elderly female participants who actively cared for their grandchildren. The results indicated a 70% increase in participants’ knowledge based on pre- and post-test results and improved skills in planning healthy family menus. This activity had a positive impact on enhancing grandmothers’ caregiving abilities and supported family-based health promotion efforts.